Composition and distribution of fish in Ba Che river, Quang Ninh province - Thuy, Ta Thi; Nhuong, Do Van; Hau, Tran Duc; Huan, Nguyen Xuan (Academia Journal of Biology, 2012)
Based on eight surveys conducted at 14 stations from the estuary to the upper reaches of Ba Che river, Quang Ninh province from August 2008 to February 2011, a total of 976 fish specimens were collected and analyzed. Of those 13 orders, 58 families, 102 genera and 123 species of fish were determined. The result reveals that eight of these species were already listed in the Red Data Book of Vietnam (2007) by CR level: Bostrichthys sinensis, Plectorhinchus gibbosus; EN level: Clupanodon thrissa, Channa maculata and VU level: Megalops cyprinoides, Nematolosa nasus, Konosirus punctatus and Parazacco vuquangensis. Of the thirdteen orders, Perciformes is the most abundant of familes, genera and species levels, and also being widely distributed from sea to freshwater. On the other hand, almost all species of Cypriformes are believed to occur in the freshwater. Not only being diverse of species composition, but there are also various marine to freshwater fishes in the research area. Particularly, of the 123 species, two freshwater fishes could be collected from the brackish water (Pseudohemiculter dispar and Sinibrama affinis). Based on the seasonal occurrence at stations, we suggested that fish distribution is abundant in the lowland, but is less dominant dispersion in midland of the river. Furthermore, marine or brackish fishes are limited to occur in lowland waters, whereas freshwater fish distribute throughout the fauna.